3D printing with AutoDesk 123D : create and print 3D objects with 123D, Autocad, and Inventor - Biehler, John (Que, 2014)
3D Printing with Autodesk Create and Print 3D Objects with 123D, AutoCAD, and Inventor Create amazing 3D-printable objects fast with Autodesk 123D! Imagine it. Then print it! Autodesk 123D gives you all the tools you need and it's free. This easy, full-color guide will help you fully master 3D printing with Autodesk 123D even if you've never done any of this before. Authors John Biehler and Bill Fane have helped thousands of people join the 3D printing revolution--now it's your turn. With step-by-step photos and simple projects, they teach you how to make the most of the whole 123D suite on Windows, Mac, and iPad. New to 3D printing? You'll learn pro techniques for creating models that print perfectly the first time. Want to start fast? Discover how to scan photos straight into your models. Don't have a 3D printer? Learn how to work with today's most popular 3D printing services. John Biehler discovered 3D printing several years ago and built his first 3D printer shortly thereafter. Since then, he's shared his 3D printing knowledge with thousands of people at live events throughout Canada and the Pacific Northwest and through online and broadcast media. He co-founded Vancouver's fastest-growing group of 3D printing enthusiasts. Bill Fane, an Autodesk Authorized Training Centre (ATC) certified instructor, has designed with AutoCAD since 1986. Fane has lectured on AutoCAD and Inventor at Autodesk University since 1995, and at Destination Desktop since 2003. He has written 220 The Learning Curve AutoCAD tutorials for CADalyst and holds 12 patents. From start to finish, 3D Printing with Autodesk 123D covers all you need to know. So stop waiting and start creating! Quickly get comfortable with the 123D workspace and key features Learn the essentials of effective 3D object design Practice 3D design hands-on with simple guided exercises Generate detailed models from photos with 123D Catch Create new 3D character "monsters" with 123D Creature Prepare any 3D model for successful printing Move from existing 3D CAD tools (if you've ever used them) Design parts that are easy to print, and multi-part models that can be printed "pre-assembled" Print through leading 3D printing services such as Shapeways, Ponoko, Fablab, and Hackerspaces